Vitamin D deficiency at pediatric intensive care admission - Corsino Rey; David Sánchez‐Arango; Jesús López‐Herce; Pablo Martínez‐Camblor; Irene García‐Hernández; Belén Prieto; Zamir Pallavicini (Elsevier, 2014)
Objective: to assess whether 25hydroxivitaminD or 25(OH)vitD deficiency has a high prevalence at pediatric intensive care unit (PICU) admission, and whether it is associated with increased prediction of mortality risk scores. Method: prospective observational study comparing 25(OH)vitD levels measured in 156 patients during the 12 hours after critical care admission with the 25(OH)vitD levels of 289 healthy children. 25(OH)vitD levels were also compared between PICU patients with pediatric risk of mortality III (PRISM III) or pediatric index of mortality 2 (PIM 2) > p75 [(group A; n = 33) vs. the others (group B; n = 123)]. Vitamin D deficiency was defined as < 20 ng/mL levels. Results: median (p25‐p75) 25(OH)vitD level was 26.0 ng/mL (19.2‐35.8) in PICU patients vs. 30.5 ng/mL (23.2‐38.6) in healthy children (p = 0.007). The prevalence of 25(OH)vitD < 20 ng/mL was 29.5% (95% CI: 22.0‐37.0) vs. 15.6% (95% CI: 12.2‐20.0) (p = 0.01). Pediatric intensive care patients presented an odds ratio (OR) for hypovitaminosis D of 2.26 (CI 95%: 1.41‐3.61). 25(OH)vitD levels were 25.4 ng/mL (CI 95%: 15.5‐36.0) in group A vs. 26.6 ng/mL (CI 95%: 19.3‐35.5) in group B (p = 0.800). Conclusions: hypovitaminosis D incidence was high in PICU patients. Hypovitaminosis D was not associated with higher prediction of risk mortality scores. Resumo: Objetivo: avaliar se a deficiência da 25‐hidroxivitamina D, ou 25 (OH) vitD, tem prevalência elevada em internações na unidade de terapia intensiva pediátrica, e se estaria relacionada à previsão de escores de risco de mortalidade. Método: estudo observacional prospectivo comparando níveis de 25 (OH) vitD de 156 pacientes, mensurados nas primeiras 12 horas da internação em terapia intensiva, com níveis de 25 (OH) vitD de 289 crianças saudáveis. Os níveis de 25 (OH) vitD também foram comparados entre pacientes na UTIP com escore PRISM III ou PIM 2 > p75 (Grupo A; n = 33), e o restante, (Grupo B; n = 123). A deficiência de vitamina D foi definida como níveis < 20 ng/mL. Resultados: o nível médio (p25‐p75) de 25 (OH) vitD foi 26,0 ng/mL (19,2‐35,8) em pacientes internados na UTIP, em comparação a 30,5 ng/mL (23,2‐38,6) em crianças saudáveis (p = 0,007). A prevalência de 25 (OH) vitD < 20 ng/mL foi de 29,5% (IC 95%, 22,0‐37,0), em comparação a 15,6% (IC 95%,12,2‐20,0) (p = 0,01). Os pacientes em terapia intensiva pediátrica apresentaram uma razão de chance (RC) para hipovitaminose D de 2,26 (IC 95%, 1,41‐3,61). Os níveis de 25 (OH) vitD foram 25,4 ng/mL (IC 95%, 15,5‐36,0) no grupo A, em comparação a 26,6 ng/mL (IC 95%, 19,3‐35,5) no grupo B (p = 0,800). Conclusões: a incidência de hipovitaminose D foi elevada em pacientes em terapia intensiva pediátrica, mas não foi associada à maior previsão de escores de risco de mortalidade. Keywords: 25 hydroxivitamin D, Critically‐ill children, Critical care, Prognostic markers, Mortality risk, Palavras‐chave: 25‐hidroxivitamina D, Crianças gravemente doentes, Terapia intensiva, Indicadores prognósticos, Risco de mortalidade